A tale behind Mum Effect - Sakgasit Ramingwong; Lachana Ramingwong (International Journal of Information Systems and Project Management, 2013)

(untitled)
Mum effect is a situation when one or more project stakeholders decide to withhold critical information for particular reasons. In software project where most of the production is intangible, the seriousness of this challenge increases exponentially. There have been reports indicating that mum effect can surface during any phase of development and ultimately lead to disaster in software projects. Mum effect can be influenced by several factors such as organizational and national cultures. This research investigates potential mum effect scenarios and reveals specific reasons which induce this challenge among information technology practitioners.